Investing in the curricular lives of educators: narrative inquiry as pedagogical medium - Latta, Margaret Macintyre; Kim, Jeong-Hee (My University, 2012)
This paper draws on the experiences of two graduate level curriculum theory classes taught at different teacher education institutions in the United States. As teacher educators and curriculum theorists, we invest in creating reflexive spaces for teachers to explore the complex terrain of lived curriculum. Narrative inquiry is chronicled as acting as an important pedagogical medium toward this aim. The purpose of the paper is to explore what practicing teachers’ narratives reveal about their curricular roles in relation to theory and practice. As participating educators consider their associated teaching identities, phenomenological notions of place are found to be fitting as they navigate understandings of lived curriculum as situated, thoughtful, and intentional. Insights generated through reflexive analysis manifest three thematic intersections: 1) Teachers confronting dissonance between theory and practice as teaching identity displacement; 2) Teachers negotiating greater implacement; and 3) Teachers moving toward embodying the creative space for teaching and learning. Renewed roles surface for teacher educators and curriculum theorists, challenging all involved to purposefully foster contexts for professional learning rather than subservience, and claim the responsibilities to provide the intellectual, emotional, and pragmatic spaces where teachers’ lived curriculum efforts can be developed and nurtured.
Keywords: Curriculum theorizing; Teacher education; Professional knowledge; Narrative inquiry